Scope Economies in the Costa Rican Banking Industry: An Analysis of the 1997–2009 Period - Gutiérrez-Li, Alejandro (2012)
The structure of the Costa Rican banking system during the period of 1997-2009is analyzed from the point of view of cost savings due to joint production versusseparated production through economies of scope. A translog cost function is estimated using panel data with thirteen banks. All the banks in the sample present economies of scope which, in addition, show a decreasing trend from the beginning of the period analyzed to its end. In general, scope economies are higher for public banks and the National Bank of Costa Rica has the highest values in the whole sampl